ASSESSMENT OF PROSPECTS FOR THE DEVELOPMENT OF SOCIAL TOURISM IN UKRAINE - Negin, E.; Bondarenko, L. (My University, 2021)
Tourism today has the character of a social orientation of the development goals of modern society. World experience shows that social tourism implements state support measures and can successfully develop in the interests of the population. The restoration of social tourism requires innovative approaches, models, directions, mechanisms and concrete measures to solve problems related to social tourism in Ukraine.
Keywords: ASSESSMENT OF PROSPECTS FOR THE DEVELOPMENT OF SOCIAL TOURISM IN UKRAINE